Participation of CSOs/NGOs in Bangladeshi climate change policy formulation: co-operation or co-optation?. Issue 6 (17th August 2016) - Lopa, Fowzia Gulshana Rashid; Ahmad, Mokbul Morshed
ABSTRACT: The Bangladesh government formulated the Bangladesh Climate Change Strategies and Action Plans (BCCSAP) in 2008 through a participatory process involving several CSOs/NGOs and others. This article discusses the participation of CSOs/NGOs in climate change policy-making, focusing on mapping their level of participation in policy-making. It demonstrates that state laws allow CSOs/NGOs to implement several projects voluntarily, but largely prohibit their participation in political decision-making processes. The state invites a few CSOs/NGOs as a condition to receive aid, but displays arbitrary and co-opting attitudes towards CSOs/NGOs that rarely ensure joint decisions in creating policy.